Les pôles de compétitivité français : un nouvel espace participant à la régulation de la relation formation/emploi ? - Catherine de Géry (Revue de la Régulation)
This article analyses the emergence of a local training/employment relationship in the French clusters. With a multiple correspondence analysis (MCA) of data relating to French clusters data, we find two groups of clusters: the first one consists of French clusters much involved in a local regulation of the training/employment relations and the second one consists of French clusters less committed. The cluster structure, the weight of SMEs and of independent firms and the SME’s in innovative and technological sectors, seems to facilitate the development of a local regulation of the training/employment relation, in the French clusters.